A case report of confusing meningoencephalocele. Issue 1 (4th December 2020) - Perrotta, Marika; Gasparroni, Giorgia; Chiavaroli, Valentina; Massimi, Luca; Cognigni, Rita; Sabatini, Laura; Topazio, Teresa; Carinci, Silvia; Sebastiani, Marianna; Mohn, Angelika; Di Valerio, Susanna
Abstract: The clinical approach plays a pivotal role in neonates with evidence of a skull mass, together with the need of monitoring unclear cases. Indeed, apparently transient alterations of the skull may be neural tube defects, which need prompt treatment. Abstract : The clinical approach plays a pivotal role in neonates with evidence of a skull mass, together with the need of monitoring unclear cases. Indeed, apparently transient alterations of the skull may be neural tube defects, which need prompt treatment.